2020
DOI: 10.1111/bjd.18942
|View full text |Cite
|
Sign up to set email alerts
|

The interferon‐γ‐induced protein 10/CXCR3 axis is associated with human herpesvirus‐6 reactivation and the development of sequelae in drug reaction with eosinophilia and systemic symptoms*

Abstract: Summary Background Drug reaction with eosinophilia and systemic symptoms (DRESS) is a condition caused by a drug‐induced immune response. Previous reports have found that CXCL10, also known as interferon‐γ‐induced protein (IP)‐10, may participate in the pathogenesis of cutaneous adverse drug reactions. However, the exact role of IP‐10 in DRESS and Stevens–Johnson syndrome (SJS)/toxic epidermal necrolysis (TEN) has remained unknown. Objectives This comparative prospective cohort study aimed to ascertain the rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 38 publications
(62 reference statements)
2
26
0
Order By: Relevance
“…Similar to the previous study, elevated plasma levels of CXCL10, an IFN‐γ‐induced chemokine, in our patient may explain the mechanism of vitiligo following DIHS. Furthermore, one study reported that the higher level of CXCL10 may play a role in DIHS with long‐term sequelae, such as Hashimoto thyroiditis 16 . Based on previous studies and our case, we postulate that dysfunction of Treg cells, reactivation of virus and elevated CXCL10 level may contribute to the development of vitiligo following DIHS.…”
Section: Discussionsupporting
confidence: 68%
“…Similar to the previous study, elevated plasma levels of CXCL10, an IFN‐γ‐induced chemokine, in our patient may explain the mechanism of vitiligo following DIHS. Furthermore, one study reported that the higher level of CXCL10 may play a role in DIHS with long‐term sequelae, such as Hashimoto thyroiditis 16 . Based on previous studies and our case, we postulate that dysfunction of Treg cells, reactivation of virus and elevated CXCL10 level may contribute to the development of vitiligo following DIHS.…”
Section: Discussionsupporting
confidence: 68%
“…In this instance, it is not to be discounted that a rare side effect, such as TEN, occurring with a not commonly associated drug, hydroxychloroquine, could have been favored by the particular immune stimulation induced by the virus SARS-CoV-2 [3]. SJS/TEN, and SCAR more generally, have been classically demonstrated to be associated with viral replication [11,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…We agree with the authors' opinion that timing is indeed an important factor that can influence rates of viral reactivation. Our previous reports 2, 3 and the studies of Japanese experts 4 all showed that reactivation of HHV-6 usually could be detected 2 to 4 weeks after the initial diagnosis. However, in addition to timing, the methods used to detect HHV-6 reactivation may also affect the results.…”
mentioning
confidence: 89%
“…We have used this method in another recent study. 3 In that study, 33 patients with DRESS received whole-blood quantitative PCR to detect the presence of HHV-6 DNA. Among them, 11 patients showed positive results (33.3%).…”
mentioning
confidence: 99%